A Phase I study to assess the safety, tolerability and pharmacokinetic profile of boceprevir and sildenafil when dosed separately and together, in healthy male volunteers. (17th February 2015) - Mora-Peris, Borja; Else, Laura; Goldmeier, David; Mears, Alison; Weston, Rosy; Cooke, Graham; Khoo, Saye; Back, David; Winston, Alan
Abstract: Objectives: Boceprevir is a first-generation direct-acting antiviral licensed for the treatment of hepatitis C infection. Sildenafil is an oral therapy for erectile dysfunction. As boceprevir is a potent inhibitor of CYP3A4, potential pharmacokinetic interactions may occur when it is coadministered with sildenafil. The aim of this study was to assess the pharmacokinetic profile of sildenafil and boceprevir when dosed separately and together in healthy volunteers. Methods: Thirteen male subjects completed the following study procedures: phase 1 (Day 0), a single dose of 25 mg of sildenafil was administered; washout period (Days 1–9); phase 2 (Days 10–15), 800 mg of boceprevir three times a day was administered; and phase 3 (Day 16), 800 mg of boceprevir and 25 mg of sildenafil were administered. All drugs were administered in the fed state. Intensive pharmacokinetic sampling was undertaken on Days 0, 15 and 16. Differences in the pharmacokinetic parameters of sildenafil, N -desmethyl-sildenafil and boceprevir between phase 3 and the earlier phases were evaluated by changes in the geometric mean ratios (GMRs). Results: All the drugs were well tolerated with no safety concerns arising. In the presence of boceprevir (phase 3 versus phase 1), the GMR for the plasma C max and the AUC24 for sildenafil increased by 1.9-fold (95% CI 1.5–2.4) and 2.7-fold (95% CI 2.1–3.4), respectively, whereas a reduction in the C max of N -desmethyl-sildenafil was observed (GMR 0.5, 95% CI 0.4–0.7). No significant changes in boceprevir exposure were observed between phases 3 and 2. Conclusions: Exposure of sildenafil is increased in the presence of boceprevir. A dose adjustment of sildenafil is therefore necessary. An initial dose of 25 mg of sildenafil is suggested.